Qualitative analysis of handedness, class participation and performance in an online mathematics class during covid-19 period (2024)
This study examined a qualitative analysis of handedness, class participation, and performance in an online mathematics class during the Covid-19 period. A qualitative method was adopted using observations and interviews to collect data during three different classes organized via a zoom online platform. Twenty-four students (12 left and 12 right-handers) were purposively and voluntarily selected based on their handedness. Five objectives were developed to guide the study. The results generally revealed no difference in the left-and right-handers’ performance in the online mathematics classes. Both the left-and right-handers learn at the same pace, participate in class discussion, and no difference was observed in both the left-and right-handers' overall performance. The study concluded that handedness has no impact on performance in online mathematics and is not a hindrance to learning in an online platform. The study recommends that since technology is having an important impact in streamlining performance in online mathematics class irrespective of handedness; there is a need for investment in online technology infrastructure; and that, social and instructional supports should be provided for all mathematics students in online classes to successfully learn with technology.